Mapping the suitability of selected crops in the Ganges Delta - Raviz, Jeny; Villano, Lorena; Aunario, Jorrel; Rala, Arnel; Balanza, Jane Girly C.; Bhattacharya, Jayanta; Mondal, Manoranjan K.; Laborte, Alice G. (International Rice Research Institute, 2023)
Assessing the suitability of different crops in specific geographic locations is crucial for optimizing crop productivity, promoting climate resilience, and guiding land use decisions. This study assessed the biophysical suitability of rice, watermelon and maize in the Ganges Delta, one of the most densely populated deltas in the world and also extremely vulnerable to climate change. This delta is expected to increasingly experience more frequent and intense extreme weather events, sea level rise and food insecurity. The suitability maps could be used in targeting alternative cropping systems, adjusting crop calendar and recommending crop management practices to increase productivity and improve the resilience of the Ganges Delta.